Family meta‐emotion and the onset of major depressive disorder in adolescence: A prospective longitudinal study. Issue 3 (26th March 2018) - Schwartz, Orli S.; Rowell, Vanessa J.; Whittle, Sarah; Byrne, Michelle L.; Simmons, Julian G.; Sheeber, Lisa; McKenzie, Vicki; Allen, Nicholas B.
Abstract: Meta‐emotion philosophy refers to an organized set of thoughts, reactions, and feelings about one's emotions and the emotions of others (Gottman, Katz, & Hooven, 1997). This study investigated the prospective relationship between family meta‐emotion processes and adolescent‐onset major depressive disorder (MDD). Adolescents (N = 198, mean age 12.5 years) and one of their parents each completed the Meta‐Emotion Interview (Katz & Gottman, 1986), and adolescents were followed‐up at ages 15, 16.5, and 19 years to assess for MDD onset. In the Meta‐Emotion Interviews, parents and adolescents were asked about both their own, and the others', anger and sadness. Results showed that parent‐report of their own meta‐emotion philosophy of sadness prospectively predicted MDD onset in adolescence, as did adolescent‐report of low parental emotion coaching in relation to sadness, and adolescent self‐perceived emotional competence in relation to sadness. Adolescents' perceptions of family emotional environments characterized by high levels of parental anger expression and family conflict also prospectively predicted MDD onset. These findings highlight the continued importance of family emotional processes in adolescence, and provide insight into how parents' and adolescents' perceptions of emotional processes within the family, particularly in relation to sadness, may be prospectively associated with risk for adolescent onset MDD.